Locomotion Characteristics and Match-Induced Impairments in Physical Performance in Male Elite Team Handball Players - Michalsik, L. B.; Aagaard, P.; Madsen, K. (International Journal of Sports Medicine, 2013)
The purpose of this study was to determine the physical demands and match-induced impairments in physical performance in male elite Team Handball (TH) players in relation to playing position. Male elite TH field players were closely observed during 6 competitive seasons. Each player (wing players: WP, pivots: PV, backcourt players: BP) was evaluated during match-play using video recording and subsequently performing locomotion match analysis. A total distance of 3 627±568 m (group means±SD) was covered per match with a total effective playing time (TPT) of 53:51±5:52 min:s, while full-time players covered 3 945±538 m. The mean speed was 6.40±1.01 km · h − 1. High-intensity running constituted only 1.7±0.9% of TPT per match corresponding to 7.9±4.9% of the total distance covered. An average of 1 482.4±312.6 activity changes per player (n=82) with 53.2±14.1 high-intensity runs were observed per match. Total distance covered was greater in BP (3 765±532 m) and WP (3 641±501 m) than PV (3 295±495 m) (p<0.05), and WP performed more high-intensity running (10.9±5.7% of total distance covered) than PV (8.5±4.3%, p<0.05) and BP (6.2±3.2%, p<0.01). The amount of high-intensity running was lower (p<0.05) in the second (130.4±38.4 m) than in the first half (155.3±47.6 m) corresponding to a decrease of 16.2%.In conclusion, modern male elite TH is a complex team sport that comprises several types of movement categories, which during match-play place moderate-to-high demands on intermittent endurance running capacity and where the amount of high-intensity running may be high during brief periods of the match. Signs of fatigue-related changes were observed in terms of temporary impaired physical performance, since the amount of high-intensity running was reduced in the second half. Notably, physical demands differed between playing positions, with WP demonstrating a more intensive activity pattern than BP and PV, respectively.
Keywords: locomotion match analysis; total distance covered; high-intensity running; positional differences; temporary impaired performance